Risk of osteoporosis and fragility fractures in asthma due to oral and inhaled corticosteroids: two population-based nested case-control studies. Issue 1 (21st October 2020) - Chalitsios, Christos V; Shaw, Dominick E; McKeever, Tricia M
Abstract : Background: Inhaled (ICS) and oral (OCS) corticosteroids are used widely in asthma; however, the risk of osteoporosis and fragility fracture (FF) due to corticosteroids in asthma is not well-established. Methods: We conducted two nested case-control studies using linked data from the Clinical Practice Research Datalink (CPRD) and Hospital Episode Statistics (HES) databases. Using an asthma cohort, we separately identified patients with osteoporosis or FF and gender-, age- and practice-matched controls. Conditional logistic regression was used to determine the association between ICS and OCS exposure, and the risk of osteoporosis or FF. The prevalence of patients receiving at least one bisphosphonate was also calculated. Results: There was a dose–response relationship between both cumulative dose and number of OCS/ICS prescriptions within the previous year, and risk of osteoporosis or FF. After adjusting for confounders, people receiving more OCS prescriptions (≥9 vs 0) had a 4.50 (95% CI 3.21 to 6.11) and 2.16 (95% CI 1.56 to 3.32) increased risk of osteoporosis and FF, respectively. For ICS (≥11 vs 0) the ORs were 1.60 (95% CI 1.22 to 2.10) and 1.31 (95% CI 1.02 to 1.68). The cumulative dose had a similar impact, with those receiving more OCS or ICS being at greater risk. The prevalence of patients taking ≥9 OCS and at least one bisphosphonate prescription was just 50.6% and 48.4% for osteoporosis and FF, respectively. Conclusions: The findings suggest that exposure to OCS or ICS is an independent risk factors for bone health in patients with asthma. Steroid administration at the lowest possible level to maintain asthma control is recommended.